(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
Betel leaf is one of the important cash crops that gaining popularity in recent time in Bangladesh. This study was conducted to identify the present and future production pattern of betel leaf in Bangladesh as well as its prospects and challenges. Secondary data of 29 years from 1991 to 2019 have been used to specify the production pattern and forecasting of betel leaf at national level by using deterministic, stochastic and dynamic time series model. While the primary data were collected from three sub-districts of the Rajshahi district namely Bagmara, Durgapur and Mohanpur to identify the prospects and challenges through SWOT analysis. This study found significant relationship among betel leaf production, price and annual average temperature of Bangladesh. A total of six growth models of different types were used for forecasting production, cultivation area, and price of betel leaf. Based on the model selection criteria cubic model, quadratic model, and growth model were chosen for initial forecasting of betel leaves production, cultivation area, and price respectively. Among the stochastic model auto regressive integrated moving average ARIMA (0, 1, 0) was fitted well to forecast the production. Finally, a dynamic regression model of ARIMA (1, 1, 0) with dynamic regressors has been used to forecast the production of betel leaf from 2020 to 2023. Forecast values range minimum 202770.41 tons to 296217.14 tons with 95% confidence interval. All the best-fitted models revealed that the production of betel leaf has an upward trend in the future. At the end SWOT analysis was implemented to identify the strengths, weakness, opportunities and threats involved in betel leaf farming which will be helpful for making future national level policy options. Diseases control at the betel leaf garden and access to credit for initial investments were identified as the major challenges for this enterprise. Res. Agric., Livest. Fish.7(2): 209-223, August 2020